The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.21273/jashs.121.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Air-filled Porosity, Gas Relative Diffusivity, and Tortuosity: Indices of Prunus ×cistena sp. Growth in Peat Substrates

Abstract: A 2-year experiment with Prunus ×cistena sp. was conducted in pots using seven substrates composed of various proportions of primarily peat, compost and bark. Peat substrates significantly affected root and shoot dry weight. Water desorption characteristics and saturated hydraulic conductivity were measured in situ to estimate the pore tortuosity factor and the relative gas diffusion coefficient. The pH, electrical conductivity, C/N ratio, total and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 18 publications
2
35
0
2
Order By: Relevance
“…However, Madsen (1976) observed that -50 cm H^O (or pF 1.7) would be a better approximate to mimic field capacity in coarse-textured media. This is also in agreement with the study by Allaire et al (1996) who used-50 cm H2O as the limiting potential of "easily available water (EAW)" for containerized media. In reduced gravity conditions, for example at Martian gravity (0.37 g), the corresponding matric potential may occur at -19 cm HjO or pF 1.3 (i.e., in equilibrium with free water held 19 cm below the gravity vector), assuming the equilibrium matric potential scales linearly with the gravitational force (Jones et al, 2011).…”
Section: Field Capacity and Critical Water Storage Windowssupporting
confidence: 92%
See 1 more Smart Citation
“…However, Madsen (1976) observed that -50 cm H^O (or pF 1.7) would be a better approximate to mimic field capacity in coarse-textured media. This is also in agreement with the study by Allaire et al (1996) who used-50 cm H2O as the limiting potential of "easily available water (EAW)" for containerized media. In reduced gravity conditions, for example at Martian gravity (0.37 g), the corresponding matric potential may occur at -19 cm HjO or pF 1.3 (i.e., in equilibrium with free water held 19 cm below the gravity vector), assuming the equilibrium matric potential scales linearly with the gravitational force (Jones et al, 2011).…”
Section: Field Capacity and Critical Water Storage Windowssupporting
confidence: 92%
“…For the limiting Earth criterion for gas diffusivity we used the value D /D^ = 0.02 reported in many studies as the threshold (minimum) value for adequate soil aeration in uncontrolled (field) conditions (Stepniewski, 1980;Schjonning et al, 2003). Jones et al (2011) used the same threshold value to discuss gas diffusivity in containerized media while Nkongolo and Caron (2006) and Allaire et al (1996) also observed a threshold nearZ) /Z)^ ~0.015 in containerized peat substrates. There is no analogous well-documented criterion for solute diffusivity/relative permittivity (E/E^, we therefore evaluated and compared die media for critical nutrient supply based on a value oíE/ £^ = 0.01, at which there is assumed to be sufficient media connectivity to fecüitate movement of solutes in root zone environments.…”
Section: Oxygen and Nutrient Diffusivities And Plant Limiting Criteriamentioning
confidence: 99%
“…According to Ghislerod (1982) and Allaire et al (1996a;1996b), the physical growth potential of a medium is not only restricted by bulk density, air-filled porosity, and water-holding capacity but also by gas exchange characteristics. According to Ghislerod (1982) and Allaire et al (1996a;1996b), the physical growth potential of a medium is not only restricted by bulk density, air-filled porosity, and water-holding capacity but also by gas exchange characteristics.…”
Section: Soil Gas Storage and Exchangementioning
confidence: 99%
“…This can be interpreted as the effect of a limited diffusivity of CO 2 and other gases at a high relative water content in the growing media. It is generally accepted that the ratio between gas diffusivity in a particular substrate and in open air is proportional to the air-filled porosity (King and Smith 1987;Bunt 1988;Allaire et al 1996). Hence, variations in the volumetric water content have a direct effect on the mobility of gases in the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In horticultural growing media, the empirical relationship between volumetric water content and the SWP often shows a plateau near water saturation (Orozco and Marfà 1995;Allaire et al 1996). The SWP at which water release begins in a saturated medium is the air-entry potential and corresponds to the SWP at which the bigger pores begin to drain (Campbell 1988).…”
Section: Discussionmentioning
confidence: 99%